Board Structure, Ownership Structure, and Performance of Thai Listed Companies - Surachai Chancharat; Nongnit Chancharat (Australasian Accounting, Business and Finance Journal, 2019)
The purpose of this paper is to investigate the effects of board and ownership structures on the performance of the companies listed on the Stock Exchange of Thailand (SET) during the period 2001-2014. A random effects panel regression analysis is employed to explore these relationships. The empirical evidence shows that the firm’s board independence is significantly related to corporate performance. Specifically, board independence has a negative and significant impact on the performance measure return on assets (ROA). The result supports the argument that outside directors will not necessarily act in shareholders’ interest since the Chief Executive Officers (CEOs) often dominate the director nomination process. Moreover, we did not find a significant relationship between other board and ownership structures and firm performance. The results from this study show how board and ownership structures influence listed firms' performance in Thailand. Firms in Thailand are generally smaller than those in developed countries, so unquestioning compliance with different codes and principles from elsewhere is inappropriate for Thai firms. The codes and principles may have to be customised to fit specific, contextual needs in Thailand.
Keywords: Board Structure; Ownership Structure; Corporate Performance; Agency Theory; Panel Regression Analysis